International Criminal Court and complementarity : from theory to practice (Vol. 2) from theory to practice - Carsten Stahn and Mohamed M. El Zeidy; Stahn, Carsten, 1971-; El Zeidy, Mohamed M. (Cambridge ; New York : Cambridge University Press, 2011)
"This systematic, contextual and practice-oriented account of complementarity explores the background and historical expectations associated with complementarity, its interpretation in prosecutorial policy and judicial practice, its context (ad hoc tribunals, universal jurisdiction, R2P) and its impact in specific situations (Colombia, Congo, Uganda, Central African Republic, Sudan and Kenya)"--Page 4 of cover.
V. 1. Introduction : bridge over troubled waters? -- pt. I. General reflections -- A positive approach to complementarity : the impact of the Office of the Prosecutor / Luis Moreno-Ocampo -- Justice and prevention / t pt. IV. Interpretation and application -- The application of the principle of complementarity to the decision of where to open an investigation : the admissibility of 'situations' / t Positive complementarity in practice : ICTY Rule 11 bis and the use of the tribunal's evidence in the Srebrenica Trials before the Bosnian War Crimes Chamber / Fidelma Donlon -- Complementarity of procedures : how to avoid reinventing the wheel / Tarik Abdulhak -- pt. VI. Complementarity in practice -- Making complementarity work : maximizing the limited role of the prosecutor / Paul F. Seils -- Positive complementarity in action / Christopher K. Hall -- Complementarity and the construction of national ability / Morten Bergsmo, Olympia Bekou and Annika Jones -- The Colombian peace process (Law 975 of 2005) and the ICC's principle of complementarity / Kai Ambos -- Darfur : complementarity as the drafters intended? / Robert Cryer -- Complementarity in Uganda : domestic diversity or international imposition? / Sarah Nouwen -- Courts, conflict and complementarity in Uganda / Marieke Wierda and Michael Otim -- Chasing cases : the ICC and the politics of state referral in the Democratic Republic of the Congo and Uganda / Phil Clark -- A problem, not a solution : complementarity in the Central African Republic and Democratic Republic of the Congo / Marlies Glasius -- Complementarity and the impact of the Rome Statute and International Criminal Court in Kenya / Christine Alai and Njonjo Mue.
Includes bibliographical references and index.
Keywords: International Criminal Court; International Criminal Court; International criminal courts; Complementarity (International law); Complementarity (International law); International criminal courts